Le temps des forêts - Drouet, Francois-Xavier; Pillosio, Raphaël; Bruckert, Agnès; Aulnette, Karine; Drouet, François-Xavier; Duchêne, Nicolas; Lazarevski, Georgi; Lévêque, Colin; Copans, Sylvain; Joly, Nicolas; Schweisguth, Bruno; Villard, Emmanuelle; et al. (France : Andana Films, 2018)
As the symbol of authentic, preserved, wild nature, forests are undergoing an unprecedented phase of industrialization. Heavy mechanization, monoculture, fertilizers and pesticides, loss of traditional know-how, forest management—all follow the intensive agricultural model at an accelerated rhythm. The Time of Forests is a journey to the heart of industrial forestry and its alternatives. A living forest or a green desert, the choices of today will define tomorrow's landscape.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films